Spiracanthus bovichthys n. gen. n. sp. (Acanthocephala: Arhythmacanthidae), a Parasite of Littoral Fishes of the Central South Coast of Chile - George-Nascimento, Mario (ResearchGate, 2015)
Artículo de publicación ISI